Pancreatic islet amyloidosis, β-cell apoptosis, and α-cell proliferation are determinants of islet remodeling in type-2 diabetic baboons - Guardado-Mendoza, Rodolfo (National Academy of Sciences, 2009)
β-Cell dysfunction is an important factor in the development of hyperglycemia of type-2 diabetes mellitus, and pancreatic islet amyloidosis (IA) has been postulated to be one of the main contributors to impaired insulin secretion. The aim of this study was to evaluate the correlation of IA with metabolic parameters and its effect on islets of Langerhans remodeling and relative endocrine-cell volume in baboons. We sequenced the amylin peptide, determined the fibrillogenic propensities, and evaluated pancreatic histology, clinical and biochemical characteristics, and endocrine cell proliferation and apoptosis in 150 baboons with different metabolic status. Amylin sequence in the baboon was 92% similar to humans and showed superimposable fibrillogenic propensities. IA severity correlated with fasting plasma glucose (FPG) (r = 0.662, P < 0.001) and HbA1c (r = 0.726, P < 0.001), as well as with free fatty acid, glucagon values, decreased homeostasis model assessment (HOMA) insulin resistance, and HOMA-B. IA severity was associated with a decreased relative β-cell volume, and increased relative α-cell volume and hyperglucagonemia. These results strongly support the concept that IA and β-cell apoptosis in concert with α-cell proliferation and hypertrophy are key determinants of islets of Langerhans “dysfunctional remodeling” and hyperglycemia in the baboon, a nonhuman primate model of type-2 diabetes mellitus. The most important determinants of IA were age and FPG (R(2) = 0.519, P < 0.0001), and different FPG levels were sensitive and specific to predict IA severity. Finally, a predictive model for islet amyloid severity was generated with age and FPG as required variables.